Karawitan Source Readings in Javanese Gamelan and Vocal Music, Volume 2 - Becker, Judith; Feinstein, Alan H. (Michigan Papers On South And Southeast Asia, 2020)
The twentieth century has spawned a great interest in Indonesian music, and now books, articles, and manuscripts can be found that expound exclusively about karawitan (the combined vocal and instrumental music of the gamelan). Scholar Judith Becker has culled several key sources on karawitan into three volumes and has translated them for the benefit of the Western student of the gamelan tradition. The texts in her collection were written over a forty-five-year time period (ca 1930-1975) and include articles by Martopangrawit, Sumarsam, Sastrapustaka, Gitosaprodjo, Sindoesawarno, Poerbapangrawit, Probohardjono, Warsadiningrat, Purbodiningrat, Poerbatjaraka, and Paku Buwana X. The final volume also contains a glossary of technical terms, an appendix of the Javanese cipher notations (titilaras kepatihan), a biographical listing, and an index to the musical pieces (Gendhing).